Climate Resilience in The Marine Ecosystems: Adaptive Strategies And Governance Models - Jeyachandran, S.; Ramesh, Krishnan (International Journal of Accounting and Economics Studies, 2025)
Climate change poses an immediate threat to aquatic systems, more so in areas where human life is intertwined with fisheries and marine biodiversity. This study constructs a climate-resilient marine management framework employing cost-efficient management techniques, adaptive governance, and inclusive economic growth models. This qualitative case study analyzes how stakeholder engagement, marine financial planning, and governance reforms can bolster resilience in marine systems. The study focuses on ecosystem service valuation (ESV) and climate finance instruments, including blue bonds and public-private partnerships, along with ESG-compliant marine planning. The analysis delves into local empowerment through capacity-building and risk-sharing frameworks. Findings reveal financial sustainability, effective institutional integration, participatory governance, and coordinated adaptive management as fundamental for attaining enduring ecological and socio-economic balance. The framework shifts the focus from marine policy conservation response to climate proactive resilience, emphasizing finance-enabled marine policy. This research expands the scope of environmental economics and marine governance to policymaking, investment, and conservation action promoting resilient ocean economies while advocating cross-border collaboration and flexible funding frameworks tailored to diverse regional contexts.